An analysis of performance in long-distance rovving by means of global positioning system technology - Cejuela, R.; Perez-Turpin, J. A.; Cortell, J. M.; Llopis, J.; Chinchilla, J. J. (International Journal of Computer Science in Sport, 2008)
The analysis of sports performance by means of technological advances has often been used to calculate the routes of sportsmen in the distances covered, or to calculate speed in orienteering. However, there is still little information on data for Global Position System (GPS) use in long-distance elite rowers. The purpose of this study was to analyze rowers' performance in a long distance fixed-seat rowing competition (14816 meters, Santa Pola, March 2007, Spain). Five boats, with eight rowers each, were used for this analysis, all with GPS technology (FRWD outdoor sports Computer series W 600, 2007). Anthropometric measurements were taken and the somatotype was calculated (3.3-3.9-2.2). The calculations included the total time for the race, distance covered by each boat, speeds, route profile, altimeter, temperature and heart rate (9,95±1,35 km x h-1, 91,53±14,13 minutes, 170+4,69 bpm). These results, added to their higher average speed, resulted in a better time in the race, and a shorter distance rowed. The coxswain's skill and experience shows itself as a performance factor in this type of event. The GPS is a suitable tool for recording data in long-distance rowing events.